Crowded Disc in a High Hyperopic Patient Misdiagnosed as Papilledema - Yadgari, Maryam; Nourizade , Parivash; Firoozian, Nina; Attarian, Behnoosh (Journal of Ophthalmic and Optometric Sciences, 2019)
A 16 year old female was referred to neurological clinic with diagnosis of papilledema for neurological evaluation. After consultation with us we became suspicious of pseudopapilledema according to refraction and biometric characteristics of the eye and the patient’s history. We performed fluorescein angiography for the patient. There was no leakage of fluorescein in images and papilledema diagnosis was rejected. The patient was diagnosed with crowded disc due to high hyperopia. This correction of diagnosis prevented the neurologist colleagues from developing the wrong diagnosis of papilledema caused by an intracranial mass, and performing any unnecessary investigations such as brain MRI or lumbar puncture. Keywords: Crowded Disc; Pseudopapilledema; Papilledema; Fluorescein Angiography.